Low‐dimensional metal halide perovskites and related optoelectronic applications. Issue 2 (6th February 2020) - Zhu, Pengchen; Zhu, Jia
Abstract: Low‐dimensional materials have pivotal significance in modern photonic, electronic, and optoelectronic areas due to their unique properties of the scale effect. Metal halide perovskites have revived in the optoelectronic fields recently, drawing intensive attention in photovoltaic devices, light‐emitting diodes, lasers, photodetectors, and so on. Compared to their three‐dimensional counterparts, the role of low‐dimensional perovskites is becoming crucial, requiring a comprehensive understanding and exploration unceasingly. In this review, we examine low‐dimensional perovskite of different forms and clarify various synthesis methods with morphological and dimensional control. Additionally, we also summarize potential optoelectronic applications based on their advantageous optical/electrical properties and enhanced mechanical integrity and stability. Finally, we propose a future perspective and possible developing directions in the exploration of novel perovskite‐derived materials, new physics, and promising applications. Abstract : This review summarizes various synthesis methods and potential optoelectronic applications of low‐dimensional metal halide perovskites. It also includes a future perspective and possible developing directions in the exploration of novel perovskite‐derived materials, new physics, and promising applications.